Cyprus : Technical Assistance Report-Debt and Cash Management. (IMF Staff Country Reports; Country Report ;, 2022)
In tandem with Eurozone financial market developments and the prevalence of negative interest rates in 2020, Cypriot banks passed through the costs of their liquidity to their customers, reducing the attractiveness of placing PDMO cash surpluses in domestic bank deposits. Suitable investment alternatives to central bank deposits for the PDMO's liquidity buffer are scarce, given negative yields on other Eurozone sovereign and agency issues. This situation is shared by the PDMO with almost all of its Eurozone peers. While this is likely to persist in the short term, it should not preclude establishing a framework governing the PDMO's investment policy or a suitable set of guidelines.